Accessibility index for urban walkable spaces - Silva, Otavio Henrique da; Pitilin, Taiany Richard; Gobbo, Caio Augusto Rabello; Caxambu, Marcelo Galeazzi; Sanches, Suely da Penha; De Angelis Neto, Generoso (Acta Scientiarum. Technology, 2019)
Considering the importance of technical accessibility parameters to the adequacy of urban areas for all people, this study aimed to develop a quantification method of pedestrian accessibility based on the technical standardization. The Accessibility of Walkable Spaces index (AWS) is composed of seven measurable indicators according to standards of accessibility, ranging from 0 (Inaccessibility) to 1 (Accessibility). After an audit of 570 sidewalk stretches in São Tomé, State of Paraná, Brazil, the Inaccessible situation was verified as the most recurrent (60.3% of the sidewalk stretches). The best conditions were found in the more consolidated urban central area, as demonstrated by the Kruskal-Wallis and Dunn tests (p < 0.05). The method showed adequate applicability. So, municipalities can use AWS index as a useful planning tool to prioritize interventions and provide inclusive and more sustainable environments to its citizens.